(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Myocardial Infarction with Non-obstructive Coronary Arteries-MINOCA is a clinical syndrome that encompasses a subgroup of heterogeneous patients who present with myocardial infarction yet do not have any significant coronary artery obstruction on angiogram. From several studies it is understood that MINOCA has a 8.8% prevalence of all Myocardial Infarction (MI) presentations, with no characteristic distinguishing clinical features when compared with MI-CAD( Coronary artery disease), except for patients being younger with a female preponderance & less likely to have hyperlipidemia. The prognosis is extremely variable, depending on the causes of MINOCA. Clinical history, echocardiography, coronary angiography, and left ventriculography represent the first-level diagnostic investigations. Ibrahim Card Med J 2015; 5 (1&2): 61-66